2022
DOI: 10.1038/s43587-022-00174-3
|View full text |Cite
|
Sign up to set email alerts
|

Healthy aging and muscle function are positively associated with NAD+ abundance in humans

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 81 publications
3
61
1
Order By: Relevance
“…The protocol below describes the procedure for polar metabolomics in human muscle biopsies ( Janssens et al., 2022 ), but the same protocol has been successfully applied for human ( Remie et al., 2021 ; Connell et al., 2021 ; Remie et al., 2020 ), mouse ( van der Stelt et al., 2021 ; Zapata-Pérez et al., 2021 ) or rat tissues (brown adipose tissue, white adipose tissue, heart, liver, kidney, brain, placenta, arterial plaque), cultured cells (primary skin fibroblasts, Human Embryonic Kidney (HEK) cells, bronchial epithelial cells, cumulus cells, oocytes, organoids), blood samples ( Zapata-Pérez et al., 2021 ) (serum, plasma, erythrocytes, platelets, peripheral blood mononuclear cells, whole blood, macrophages), other bodily fluids (saliva, sweat, urine, fecal water, bile, cerebrospinal fluid), model organisms ( Molenaars et al., 2021 ; Liu et al., 2020 ; Gao et al., 2018 ; Molenaars et al., 2020 ) (yeast, fruit flies, zebrafish and C. elegans) and culture medium. Additional details on these matrices can be found in Table S1 Sample Matrix Overview.…”
Section: Before You Beginmentioning
confidence: 99%
See 3 more Smart Citations
“…The protocol below describes the procedure for polar metabolomics in human muscle biopsies ( Janssens et al., 2022 ), but the same protocol has been successfully applied for human ( Remie et al., 2021 ; Connell et al., 2021 ; Remie et al., 2020 ), mouse ( van der Stelt et al., 2021 ; Zapata-Pérez et al., 2021 ) or rat tissues (brown adipose tissue, white adipose tissue, heart, liver, kidney, brain, placenta, arterial plaque), cultured cells (primary skin fibroblasts, Human Embryonic Kidney (HEK) cells, bronchial epithelial cells, cumulus cells, oocytes, organoids), blood samples ( Zapata-Pérez et al., 2021 ) (serum, plasma, erythrocytes, platelets, peripheral blood mononuclear cells, whole blood, macrophages), other bodily fluids (saliva, sweat, urine, fecal water, bile, cerebrospinal fluid), model organisms ( Molenaars et al., 2021 ; Liu et al., 2020 ; Gao et al., 2018 ; Molenaars et al., 2020 ) (yeast, fruit flies, zebrafish and C. elegans) and culture medium. Additional details on these matrices can be found in Table S1 Sample Matrix Overview.…”
Section: Before You Beginmentioning
confidence: 99%
“…Human muscle biopsies were obtained as part of a previous study ( Grevendonk et al., 2021 ; Janssens et al., 2022 ). Research was approved by the institutional medical ethical committee, and experiments were conducted in agreement with the Declaration of Helsinki.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, low NAD + levels have been linked to multiple disease states, therefore NAD + -boosting approaches have been proposed as a potential therapeutic strategy against various diseases 24 . In fact, increasing evidences suggest that NAD + -boosting strategies can improve physiological and metabolic health in rodent models of ageing, obesity, and diabetes 5,6 , and recent clinical studies suggested a clear association between NAD + and physiological status during human aging 7 and disease progression 8 .…”
Section: Introductionmentioning
confidence: 99%